Microminerais orgânicos para codornas japonesas - Carvalho, Ronaldo Barcellos de (2015)
This study aimed to evaluate the performance and egg quality of Japanese quails, due to the reduction and partial or total replacement of trace minerals (manganese, zinc, iron, copper, iodine and selenium) to replace the organic trace mineral inorganic. Two experiments were conducted in the poultry sector of the Instituto Federal do Espírito Santo, which lasted 84 days, divided into four periods of 21 days. In each experiment, 480 Japanese female quails were used, with 79 days old. The birds were distributed in a completely randomized design in 6 treatments, 10 replicates and eight birds each. The same basal diet in both experiments, varying only the levels and the source of trace minerals used was used. In the first experiment has been added to this feed five different levels of organic trace minerals 25; 50; 75; 100 and 125% of the organic and mineral complex recommendation level with inorganic trace elements (100% recommended) used being 1 kg / ton feed. In the second experiment, were added four different levels of mixture of organic and inorganic trace minerals (20% organic + 80% inorganic, 40% organic + 60% inorganic, organic + 60% 40% 80% inorganic and organic + 20% inorganic) an inorganic (100%) and an organic (100%) in the diet. The characteristics were feed intake, egg production, average egg weight, egg mass, feed conversion per egg mass and per dozen eggs, relative and absolute yolk, albumen and shell, in addition to the unit Haugh. The evaluated parameters were not significantly affected by the different relations of use of organic and inorganic minerals. It was observed that can be reduced to 25% of trace minerals recommendation when it is used organic trace minerals and it is possible to replace up to 100% of inorganic trace minerals by organic without effect on the productive performance and the quality of quails Japanese.